Human immunodeficiency virus infection in children, special aspects - Sunarto, Sunarto (Universitas Gadjah Mada, 1998)
Human immunodeficiency virus infection in children and infants has some different characteristics compared to that in adults, including the transmission, the clinical manifestations and the clinical course. Many factors are associated with the vertical transmission, among others are maternal antigen p24 level, viral load, CD4+ -cell number, zidovudine therapy, and the presence of anti-Gp 120. Growth and development failure, interstitial pneumonia, and hepatomegaly are found in almost all pediatric AIDS. Lymphoid interstitial pneumonia (LIP) has a high frequency in vertical AIDS. Pneumocystic carinii pneumonia (PCP) as early complication occurs in about 10% of children with AIDS and has high mortality. Gastrohepatobillary dysfunction caused by various opportunistic microorganisms are common; disaccharidase intolerance also frequently occurs. The longer the children alive the higher the cardiac abnormalities. Neurologic abnormalities are found in 90% of vertical AIDS. The clinical course and the prognosis of vertical infection is associated with the maternal virus load, symptomatic HIV and p24 antigenemia, the lower the CD4+ cells in the mother, and the characteristic of the virus. The increased p24 antigenemia in the first 6 months of life, the opportunistic infections, and the progressive neurologic disease are related also to bad prognosis. Laboratory based diagnosis of HIV infection in infants is difficult especially due to the presence of maternal antibody. A number of tests is now under studies to find reliable and practical diagnostics, including polymerase chain reaction (PCR) of liquid or dried blood samples. IgA and other practical kit tests. HIV infected children show lower response against vaccinal antigens than normal infants. Anyhow, vaccination with killed vaccines is recommended for all HIV infected infants, including diphtheria, tetanus, killed polio. HIV infected children show response against H. influenzae vaccine. The advantages of BCG vaccination are weighted against the disadvantages. Varicella and hepatitis-B vaccine effectivity need further studies.Key words: pediatric HIV - vertical transmission - clinical manifestation - prognostic factor - laboratory diagnostics - recommended vaccination